JACO VAN SCHALKWYK’S PAINTING SKILL TRANSFER IN “PAINTING WORKSHOP AND CONCEPTUAL THINKING” AT GALLERY OF FBS, UNDIKSHA 2020 - Agus Sudarmawan (Universitas Pendidikan Ganesha, 2022)
Abstract It was necessary to thoroughly review Jaco Van Schalkwyk’s painting skill transfer, an African painter, through an instructional development in a non-formal educational system. Skill transfer needed to be developed for transfer of knowledge/concepts, skills and appreciation of painting in the educational world, especially Fine Arts in as society of academicians’ form of development. Morespecifically, this research aimed to analyse skill transfer development process, tools and materials used and tangible skill transfer results of painting works developed by Jaco Van Schalkwyk. The research method used was descriptive qualitative method, and the data were collected through observation, interview, literature and documentation techniques. The Jaco Van Schalkwyk’s Skills Transfer Process included the following stages: 1. Introduction; was about self- introduction and cosmology of cultural climate on which art practices were based on. 2. Observation; trained learners’ artistic sensitivity, broadening their stimuli in finding new ideas of work. 3. Discussion; sharpened analytical reasoning and interpretation. 4. Idea Execution; recorded information of arising ideas. 5. Monitoring and Evaluation; solution to confusion. 6. Demonstration; trained the sensitivity to shape and motor sensitivity through Live Model Painting. 7. Presentation; trained responsibility for self-creativity. Based on the seven stages, we may conclude that skill transfer started with the biography related to how exploration of painting theme continued with responding to surrounding objects tobe taken as the source of painting idea.Keywords: painting, skill transfer, conceptual